Evolving practices to improve student performance and efficiency in competency‐based postsecondary technical training. Issue 2 (11th April 2020) - Cummings, Kevin; Stephens, Terri; Horne, Owen
Abstract : The Davis Technical College pioneered competency‐based vocational/technical education. The institution's early model allowed students freedom to create their own schedule and to move at their own pace, but proved ineffective at encouraging students to be efficient in completing their training. A sharp increase in enrollment in the early 2000s drove the college to revise the model which resulted in increased efficiency and, thus, higher throughput.